Strategi Marketing dalam Meningkatkan Market Share Produk Tabungan Wadi’ah, di PT BPRS Mentari Pasaman Saiyo Siswa Kelas VIII SMPN 7 Bukittinggi - Hennia Azzahra; Harfandi (ARZUSIN, 2026)
Although marketing strategies for increasing the market share of wadi’ah savings products at Sharia Rural Banks have been widely studied, research specifically analyzing these strategies based on a SWOT analysis at PT BPRS Mentari Pasaman Saiyo remains limited. This study aimed to analyze marketing strategies for increasing the market share of wadi’ah savings products by identifying the company’s internal and external factors. The study employed a qualitative approach with a case study design. Informants were selected through purposive sampling and consisted of the management, marketing personnel, and customers of PT BPRS Mentari Pasaman Saiyo. Data were collected through observation, semistructured interviews, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña combined with SWOT analysis. The results showed that the marketing strategies implemented included personal selling, improvement of service quality, promotion to the public, and strengthening relationships with customers. The SWOT analysis showed that the company’s strengths included service quality and public trust, whereas its weaknesses included limited human resources in marketing and suboptimal digital promotion. The company’s opportunities arose from increasing public interest in Islamic banking, while its primary threats included interbank competition and the development of digital banking services. These findings emphasize that increasing the market share of wadi’ah savings products requires marketing strategies that optimize service quality and public trust while strengthening human resource capacity and digital promotion. This study contributes to the development of research on SWOT-based marketing strategies in the context of Islamic banking and provides practical implications for PT BPRS Mentari Pasaman Saiyo in formulating more effective and adaptive marketing strategies.